Behçet’s Syndrome Overall Damage Index performance and validation in an adult Egyptian cohort - Doaa Attia; Lobna Maged (Archives of Rheumatology, 2024)
Objectives: This study aimed to evaluate the performance of the Behçet’s Syndrome Overall Damage Index (BODI) in an adult Egyptian cohort. Patients and methods: This longitudinal retrospective cohort study included 282 adult patients (233 males, 49 females; mean age: 35.3±8.7 years; range, 16 to 66 years) with Behçet’s disease (BD) between January 1980 and December 2022. BODI was assessed regarding construct validity, sensitivity to change, and intra- and inter-rater reliability. The ability of BODI to discriminate between activity and damage was evaluated. Its performance in another vasculitis syndrome was assessed in 12 patients with antineutrophil cytoplasmic antibody-associated vasculitis. Results: BODI captured more damage items compared to the Vasculitis Damage Index (VDI). BODI scores were not correlated with disease activity and had poor performance in other vasculitides. BODI had a trend of progressive increment over time. It showed consistence when reassessed by the same rater and by different raters. Some damage items in the study cohort were lacking in BODI. Conclusion: BODI is more comprehensive compared to VDI. It shows good face, construct, and discriminant validity. It is sensitive to change and has good intra- and inter-rater reliability. Newer versions of BODI are recommended to increase score comprehensiveness.